METODE FUZZY ANALYTICAL HIERARCHY PROCESS DALAM METODE PERFORMANCE APPRAISAL UNTUK MENENTUKAN TINGKAT KUALITAS DOSEN PADA JURUSAN AKUNTANSI POLITEKNIK NEGERI BANJARMASIN - HERU KARTIKA CANDRA; Ronny Mantala; Said Muhammad; Slamet Riyadhi (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2018)
The measure of the success of a lecturer in transferring his knowledge to students becomes the main focus so that it can be described in a measurable manner, so that what is given can be understood, accepted and applied by students in accordance with the objectives to be achieved, namely the quality of teaching. Almost all universities assess their teaching performance. Performance appraisal means evaluating the current and / or past teaching quality relative to its performance standards. Some reasons for assessing teacher quality, first is integrated in the performance management process, second is assessment allows superiors and subordinates to develop a plan to correct all deficiencies found, third is assessment needed to know the strengths and weaknesses of teachers that are useful for career planning for teachers itself. There are several tools that are commonly used to conduct teacher performance assessments, namely the performance appraisal method. However, performance appraisal has several weaknesses (Dessler, 2008) including: subjective assessment, halo effect, centralized tendency, influenced by age, race and gender. Therefore, a technical evaluation system for performance appraisal is needed, so that it can get a more accountable assessment. In the previous research conducted by the author, the method used in the measurement process with parameters in the performance appraisal method is by using the Fuzzy Mamdani Logic method where the aim is to assess teacher performance by improving the assessment method of performance appraisal from the parameters, so can be used as a decision support system. The results obtained in the measurement with Fuzzy Mamdani Logic method are seen from the accuracy level of 60% accuracy of the calculation compared to the use of performance appraisal method. After developing the method that is by using the method of Fuzzy Analiytic Hierarchi Process the results obtained can increase the level of calculation accuracy up to 93%, considering in the FAHP method, the parameters that become the calculation variable will be analyzed first the level of consistency so that it is feasible to use.